Ethics and Power: Niccolo Machiavelli's thoughts on Ethics and Power in Politics - Haikal Mujahid (The International Journal of Politics and Sociology Research, 2020)
Ethics is a science that seeks orientation for human efforts to answer a very fundamental question, how should I live and act. Meanwhile, power is the effort of an individual or group to influence others according to the wishes of the perpetrator. Ethics and power are two very important positions in the political frame. even these two terms have been discussed since ancient Greece, because they can affect the running of the government. Because if these two terms are not used in their capacity, this will result in the instability of a country, or even give birth to a rebellion. Machiavelli as a political figure in the Renaissance era has succeeded in creating a work that combines the royal system (monarchy) and the Republic. which he titled The Prince and The Discaurses, although at first they were addressed to the Medici family who regained control of Florence. From these two books, lessons can be drawn on how a leader (King) should control, manage, and take care of the staff, as well as the people in order to create a prosperous country, and be able to achieve glory, and be respected by the people and other countries. The concept of "justifying all means" that many people know from Machiavelli seems to have become a label for him. Yet we ourselves have not tried to study Machiavelli's political concepts in detail. And we also don't know why many world dictators use the Machiavelli concept in realizing practical politics in their countries, which are implemented with an iron fist. Do they actually use this Machiavelli concept kaffah (totally), or only half-heartedly in order to preserve their power? Because Machiavelli once said that the purpose of power is only for the sake of maintaining stability, and the welfare of the country, not only for individual interests.